Analysis of students’ problem solving abilities with symbolic representation through the implementation of the case method - SITUMORANG, PRIMA LESTARI (Education and Social Sciences Review, 2025)
This study aims to analyze problem-solving abilities with Symbolic representative in Economic. This study was conducted on 50 students of economic education of Musamus University and then an analysis was carried out on the results of solving problems for 5 respondents according to the qualifications of Very Good, Good, Enough, Bad, Worst . The type of this research is Qualitative Research with a case study approach. The research instruments used in collecting data are observations of students activities, Tests, Interviews, and Documentation. The analysis stage of problem- solving ability uses stage analysis by Polya while the analysis of symbolic representation ability uses Fatqurhohman. The study results indicate that students' problem-solving ability is quite good for the following reasons: 1. The Students can identify information based on the problems given. 2. The students have been able to plan problem - solving and change it into mathematical symbols. 3. In general, The students have been able to simplify and change mathematical calculations but there are still errors in analyzing the final value. 4. The students are still unable to conclude and describe the relationship between findings and images in graphic sketches. 5. The importance of Teacher in carrying out varied learning innovations to create collaboration and learning participation.